2008
DOI: 10.1111/j.1365-2109.2008.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rice straw and bamboo stick substrates in periphyton-based carp polyculture systems

Abstract: An experiment was conducted to compare rice straw mat and kanchi (bamboo sticks) as substrates in periphyton-based polyculture systems. The experiment had three treatments: (a) no substrate (control), (b) rice straw as a substrate (3 Â 2.7 kg pond À1 ) and (c) kanchi as a substrate (390 kanchi pond À1 ). Fingerlings (n 5 40) of rohu, Labeo rohita (24.5 AE 0.5 g); mrigal, Cirrhinus mrigala (25.1 AE 0.6 g); catla, Catla catla (25.8 AE 0.5 g); common carp, Cyprinus carpio (27.6 AE 0.6 g), and silver carp, Hypopht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
2
10
1
2
Order By: Relevance
“…8% (Table 2) respectively. Similar results like the periphytic differences due to substrates observed by Wahab et al (1999), Rai et al (2008Rai et al ( , 2010 and Hosain et al (2011). Copepoda: Copepods constituted 6% of total zooperiphyton (Fig.…”
Section: Resultssupporting
confidence: 84%
“…8% (Table 2) respectively. Similar results like the periphytic differences due to substrates observed by Wahab et al (1999), Rai et al (2008Rai et al ( , 2010 and Hosain et al (2011). Copepoda: Copepods constituted 6% of total zooperiphyton (Fig.…”
Section: Resultssupporting
confidence: 84%
“…The periphytic forms are considered as both a trophic resource and indicator of the environmental conditions (Azim et al, 2005;Rai et al, 2008). The ponds were stocked with carp fingerlings with a stocking density at 5000/ha with daily manuring.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it is expensive for marginal poor farmers. Rai et al [85] reported higher amount of periphytic bacteria on rice straw (41 320 million cfu m ). The stocked fishes (rohu, catla and common carp) in his experiment attained 38% and 47% higher combined total weight in substrate-based environment than to substrate free control.…”
Section: Self-substrating To Rice-fish Culturementioning
confidence: 99%
“…The gross margin analysis showed that rice straw resulted in more profit than kanchi substrate type. Therefore, Rai et al [85] advocated the use of rice straw as the potential and low input substrate to be used to increase fish production in rural aquaculture. In Apatani Plateau, it was calculated out that the rice stems provide an additional surface area of more than 1000m 2 for the local cultivar 'amo' with stem diameter of 1.0-1.3cm submerged into 20-30cm water in the field.…”
Section: Self-substrating To Rice-fish Culturementioning
confidence: 99%